Analysis Of The Effect Of Penstock Diameter Variation And Nozzle Flow Velocity On Pelton Turbine Performance Using Computational Fluid Dynamics (CFD) - Revaldo Nur Hidayat; Randi Purnama Putra; Yolli Fernanda; Fitrah Qalbina (Unversitas Negeri Padang, 2026)
The performance of a Pelton turbine in micro-hydropower plants is influenced by penstock design and fluid flow conditions. Variations in penstock diameter can lead to changes in head loss, flow velocity, and energy transfer efficiency. This study aims to analyze the effect of penstock diameter variation and nozzle flow velocity on Pelton turbine performance under different head conditions using the Computational Fluid Dynamics (CFD) method.Simulations were conducted using penstock diameters of 4 inches, 5 inches, and 6 inches with ANSYS software. The results show that the respective head losses are 0.010 m, 0.006 m, and 0.0028 m, indicating that larger diameters reduce friction losses in the flow. The corresponding nozzle velocities are 8.90 m/s, 9.08 m/s, and 8.64 m/s, with the highest value observed at the 5-inch diameter due to the balance between flow rate and energy losses. The resulting torque values are 2.13 Nm, 2.55 Nm, and 2.60 Nm, while the rotor rotational speeds are 150.87 W, 189.07 W, and 194.90 W. The effective power generated is 65.59 W, 80.21 W, and 77.79 W, with efficiencies of 43.77%, 42.44%, and 39.95%, respectively. The results indicate that a 5-inch penstock diameter provides the most optimal performance, as it achieves the best balance between head loss, flow distribution, and fluid energy transfer.